From Vitality to Creativity: The Mindful Pathway in the Workplace - Billah Karima; Endang Parahyanti (Dinasti Publisher, 2025)
Creativity is a vital competitive asset for companies, supported by extensive research on employee creativity. While most studies adopt a top-down approach, this research explores a bottom-up perspective, examining how individuals enhance creativity through proactive vitality management. Using a quantitative non-experimental method, the study involved 371 creative professionals in Indonesia, analyzed through Structural Equation Modeling - Partial Least Square (SEM-PLS). Results reveal that proactive vitality management significantly boosts employee creativity (? = .676, p = .000). Additionally, mindfulness positively mediates the relationship between vitality management and creativity (? = .119, p = .002). This study provides practical insights for creative professionals on managing energy to foster innovation and contributes theoretically to human resource management by uncovering the dynamics between vitality management, mindfulness, and creativity. Emphasizing self-driven approaches, the research offers valuable perspectives for enhancing workplace creativity, benefiting both practitioners and scholars.